THE EFFECT OF THERMAL STRESS AND MATERIALS TOWARDS STRAY GASSING FORMATION IN UNINHIBITED AND INHIBITED OIL (Jurnal Teknologi (Sciences & Engineering), 2022)
Insulation oil is one of the most important components in an oil-insulated transformer. With the use of the dissolved gas analysis (DGA) tool, the condition of the transformer can be studied and predicted to prevent unwanted events from occurring. However, due to the rising of issues related to stray gassing phenomenon that causes false interpretations in the transformer condition, there is a need to find out the factors contributing to the formation of the stray gases in the transformer oil. In this research paper, thermal stress (85℃ and 120℃) on transformer oil with different transformer materials are studied to determine the effect towards the formation of stray gases in the transformer oil. The materials studied include diamond dotted paper, metal plate, coated metal plate, insulation glue and core metal. Both the uninhibited oil and inhibited oil are used for comparison. The metal plate, coated metal plate and core metal were found to be causing the generation of H2 gas at 120℃ while the cellulose ageing of insulation paper is causing the generation of CO and CO2 gases at 85℃ and above. The CH4 gas was found to be generated only at 120℃ and the insulation glue was determined to be the main cause for the C2H4 gas generation at 85℃ and above.